Comparing the Ptolemaic and Seleucid Empires (Cambridge, UK ; New York)
xiv, 390 sayfa, [3] sayfa harita
Keywords: “The Ptolemaic and Seleucid empires are usually studied separately, or else included in broader examinations of the Hellenistic world. This book provides a systematic comparison of the roles of local elites and local populations in the construction, negotiation, and adaptation of political, economic, military and ideological power within these states in formation. The two states, conceived as multiethnic empires, are sufficiently similar to make comparisons valid, while the process of comparison highlights and better explains differences. Regions that were successively incorporated into the Ptolemaic and the Seleucid state receive particular attention and are understood within the broader picture of the ruling strategies of both empires. The book focuses on forms of communication through coins, inscriptions and visual culture; settlement policies and the relationship between local and immigrant populations; and the forms of collaboration with and resistance of local elites against immigrant populations and government institutions.“--